Do Big Data and Auditor Experience Matter? Assessing Fraud Detection with Forensic Audits as a Key Mediator - Sugeng Riadi; Vitra Desaina Ginting (UNIB Press, 2025)
With advancements in data technology and the growing complexity of financial fraud, questions arise about the impact of Big Data and auditor experience on effective fraud detection. This study delves into the role of Big Data and auditor expertise in enhancing fraud detection and the effectiveness of forensic auditing, focusing on forensic auditing's potential as a mediating factor. Surveying 157 government auditors from Indonesia's Audit Board, the Financial and Development Supervisory Agency, the Financial Services Authority, and the Inspectorate General of the Riau Islands Regency. Data was collected through questionnaires and analyzed via PLS-SEM using Smart-PLS 3. The findings indicate that Big Data and auditor experience significantly bolster fraud detection and forensic auditing. However, contrary to expectations, forensic auditing does not directly influence fraud detection nor serves as a mediator in the relationship between Big Data and auditor experience in fraud detection. These insights underscore the independent yet complementary roles of Big Data and auditor expertise in fraud detection practices.